Tomographical analysis of electrochemical lithiation and delithiation of LiNi0.6Co0.2Mn0.2O2 cathodes in all-solid-state batteries. (May 2019) - Choi, Sungjun; Yun, Bin-Na; Jung, Wo Dum; Kim, Tae Hyun; Chung, Kyung-Yoon; Son, Ji-Won; Sang, Byoung-In; Jung, Hun-Gi; Kim, Hyoungchul
Abstract: We demonstrated the use of three-dimensional (3D) atom-probe tomography (APT) for analyzing the electrochemical lithiation/delithiation in the composite cathodes of all-solid-state batteries (ASSBs). 3D APT provides direct determination of the Li-ion contents, having difficult by X-ray excitation. Compared with various cathodes, they showed a significant variation in the Li-ion concentration during lithiation/delithiation because of the poor solid-to-solid interfaces, which is an inherent problem in ASSBs. In addition, the loss of transition-metal content was quantitatively verified. We have confirmed that our APT can be effectively applied to ASSB systems and it would be provide a deeper understanding of electrochemistry in ASSBs. Graphical abstract: Unlabelled Image